PROFIL PENDERITA SKABIES DI PUSKESMAS SUNGAI PINANG KABUPATEN HULU SUNGAI SELATAN PERIODE 2020-2022 - Fayujana, Astri Meliani; Hadi, Sukses; Sanyoto, Didik Dwi; Essary, Erika Dewi; Wydiamala, Erida (Universitas Lambung Mangkurat, 2024)
Abstract: Scabies is a skin infection caused by sensitization and infestation of the Sarcoptes scabiei var. Hominis mite. It is one of the most common skin diseases and ranks third among the 12 most common skin diseases in Indonesia. The occurrence of scabies is mainly influenced by environmental cleanliness, age, gender, knowledge about scabies, and personal hygiene. The purpose of the study mentioned is to determine the profile of scabies patients at the Sungai Pinang Community Health Center in Hulu Sungai Selatan Regency during the period of 2020-2022. The study used observational descriptive research design and analyzed medical records and electronic data of scabies patients. The study found a total of 691 scabies patients, with the highest number of cases in 2022 (55.2%). The age group with the highest number of cases was 6-11 years old (25.1%), and females accounted for the majority of cases (51.8%). Most scabies patients came from Banua Hanyar village (31.8%), and the most common occupation was students (41.5%). The most frequently given treatment was a combination of topical and systemic medications (74.3%). In conclusion, scabies often occurs in children aged 6-11 years, with females being the most affected. The majority of patients come from Banua Hanyar village and are students. The study also showed that the majority of treatments involved a combination of topical and systemic medications. Keywords: health centers, personal hygiene, students, scabies Abstrak: Skabies merupakan penyakit infeksi kulit yang disebabkan oleh sensitisasi dan infestasi tungau Sarcoptes Scabiei var. Hominis. Skabies merupakan salah satu penyakit kulit yang paling umum terjadi dan menempati urutan ketiga dari 12 penyakit kulit yang paling umum di Indonesia. Munculnya penyakit skabies terutama dipengaruhi oleh kebersihan lingkungan, usia, jenis kelamin, pengetahuan tentang penyakit skabies dan kebersihan diri. Penelitian ini bertujuan untuk mengetahui profil penderita skabies di Puskesmas Sungai Pinang Kabupaten Hulu Sungai Selatan periode 2020-2022. Penelitian ini merupakan penelitian observasional deskriptif menggunakan rekam medis pasien skabies dan data elektronik. Penelitian ini mendapatkan hasil 691 pasien skabies, tertinggi pada tahun 2022 (55,2%). Kelompok usia terbanyak ialah 6-11 (25,1%), perempuan jadi kasus terbanyak (51,8%). Mayoritas pasien skabies berasal dari desa Banua Hanyar (31,8%). Pekerjaan terbanyak yaitu pelajar (41,5%). Pengobatan yang paling sering diberikan adalah kombinasi obat topikal dan sistemik (74,3%). Kesimpulan penelitian ini yaitu skabies sering terjadi pada anak-anak dengan rentang usia 6-11 tahun dan perempuan menjadi kasus terbanyak. Mayoritas pasien berasal dari desa Banua Hanyar dan berstatus pelajar. Penelitian ini menunjukkan bahwa sebagian besar pengobatan menggunakan kombinasi obat topikal dan sistemik. Kata-kata kunci : puskesmas, kebersihan diri, pelajar, skabies